Feasibility Study of Ice Crystal Business for Rural and Marketing Innovation in Boyolali Regency - Suwartono, Adhi; Purwoko, Sigit Djalu (Lembaga Riset Mutiara Akbar (LARISMA), 2022)
The growth of business actors in the contemporary beverage sector is seen in urban and rural areas. Various brands and variations of raw materials. This is one of the points in the results of the SWOT analysis. This study was prepared with the aim of assessing the business feasibility of a company that becomes a retailer agent in one of the sub-districts in Boyolali district, Central Java province. Assessing several aspects such as business aspects, marketing aspects, operational aspects, human resources aspects, financial aspects, juridical aspects, and environmental aspects. The results of the study indicate that increasing the company's ability to produce ice crystals independently through investment in production machines and innovations in the marketing field will be carried out is feasible. Companies need to maintain the quality of products and services that have been running well.